Mga Alagad ng sining ([S.l. s.n.])
A documentary of 1992 Urian award winners who were acknowledged for their remarkable cultural contributions.
VHS
Urian awards held on April 11, 1992 taped from a Philippine TV station.
Narrators, Sheryl Cruz and Kris Aquino.
Keywords: Artists -- Philippines; Literary prizes -- Philippines; Philipine literature